Threat of extinction of Macrobrachium esculentum in the Serayu River (Central Java, Indonesia) confirmed by DNA barcoding - BARUNA KUSUMA; SLAMET BUDI PRAYITNO; ANINDITIA SABDANINGSIH; PETRUS HARY TJAHJA SOEDIBYA; SURADI W. SAPUTRA (Society for Indonesian Biodiversity, 2024)
Abstract. Kusuma B, Prayitno SB, Sabdaningsih A, Soedibya PHT, Saputra SW. 2024. Threat of extinction of Macrobrachium esculentum in the Serayu River (Central Java, Indonesia) confirmed by DNA barcoding. Biodiversitas 25: 3531-3539. Sweet river prawn (Macrobrachium esculentum Thallwitz 1891 is one of the amphidromous shrimp. Serayu River is one of the habitats of this shrimp. Information about the M. esculentum in the Serayu River, is still minimal, so this research is essential. The Serayu Weir affects the population of Macrobrachium esculentum, which impacts the balance of the Serayu River ecosystem. This study aims to determine the condition of the M. esculentum population in the lower reaches of the Serayu River in order to maintain its sustainability and avoid the threat of extinction. This research was conducted for one year (January-December 2023). The method used was the descriptive method. We collected M. esculentum catches both upstream and downstream of the weir for one year to determine the presence of shrimp as a result of the Serayu Weir. The catch data was compared with the catch data from previous research. M. esculentum has morphological characteristics with a blackish-gray pattern with stripes along its abdomen and has an upper rostrum of 11-14 teeth and 2-4 on the lower rostrum. M. esculentum in the Serayu River has an mtDNA fragment of 686 bp and shows the same species as M. esculentum in GenBank. A total of 65 M. esculentum were collected. This shrimp was not found above the weir (Station 1) but only at station 2 (below the weir) due to the presence of weir. The results showed the importance of constructing migration routes for aquatic biota in the Serayu Weir. Further research is also needed, especially related to the reproductive system of M. esculentum.